Correlation The Level of Nutritional Knowledge, Breakfast Consumption Patterns With Nutritional Status of Age Students 10-12 MI Dakwatul Khoiriyah Kediri - Amanda Hamidah; Riezky Faisal Nugroho; Mujayanto; Inne Soesanti; Sharifah Intan Zainun Sharif Ishak (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Children aged 10–12 years need significant energy due to their rapid growth and active lifestyles. Their nutritional status is influenced by nutritional knowledge and breakfast habits. To examine the relationship between nutritional knowledge, breakfast habits, and nutritional status of students aged 10–12 years at MI Dakwatul Khoiriyah Kediri. A cross-sectional study with 40 students using questionnaires for nutritional knowledge, SQ-FFQ interviews to evaluate breakfast habits, and BMI for age index to determine nutritional status. Spearman correlation tests were used for analysis. The study found that 62.5% had low nutritional knowledge, 60% had infrequent breakfast habits, and 65% were malnourished. There is a significant relationship between the level of nutritional knowledge and nutritional status (p=0.000, r=0.688) and between the habit of rarely eating breakfast and poor nutritional status (p=0.000, r=0.812). There is a significant relationship between nutritional knowledge, breakfast habits, and nutritional status of students aged 10–12 years at MI Dakwatul Khoiriyah Kediri. Students should have daily breakfast to meet nutritional needs and improve nutritional status.